Physical Activity, Sedentary Behavior, Sleep and Self-Regulation in Spanish Preschoolers during the COVID-19 Lockdown - Alonso-Martínez, Alicia M.; Ramírez-Vélez, Robinson; García-Alonso, Yesenia; Izquierdo, Mikel; García-Hermoso, Antonio (International journal of environmental research and public health, 2021)
Background: A better understanding of the effects of the lockdown on lifestyle behaviors may help to guide the public health response to COVID-19 at a national level and to update the global strategy to respond COVID-19 pandemic. The aim of the study was to examine the effects of the COVID-19 lockdown on device-measured physical activity (PA), sedentary time, sleep and self-regulation; and to determine whether PA and sleep are related to self-regulation problems during the lockdown. Methods: PA, sedentary time and sleep were assessed using accelerometry in the week in which the Spanish national state of alarm was declared (n = 21). Parents reported preschooler’s self-regulation difficulties (internalizing and externalizing) before (n = 268) and during the lockdown (n = 157) by a validated questionnaire. Results: Preschoolers showed a decrease in total PA (mean difference [MD] = −43.3 min per day, 95% CI −68.1 to −18.5), sleep efficiency (MD = −2.09%, 95% CI −4.12 to −0.05), an increase in sedentary time (MD = 50.2 min per day, 95% CI 17.1 to 83.3) internalizing (MD = 0.17, 95% CI 0.06 to 0.28) and externalizing (MD = 0.33, 95% CI 0.23 to 0.44) problems. Preschoolers who met the World Health Organization recommendations for PA had lower internalizing scores than non-active peers (MD = −1.28, 95% CI −2.53 to −0.03). Conclusions: Our findings highlight the importance of meeting PA recommendations to reduce psychosocial difficulties during a lockdown situation.